Thermo-economic assessment of upgrading a basic gas turbine power plant into CHP plant. (11th April 2023) - Aberkane, Sofiane; Semmari, Hamza; Filali, Abdelkader; Rebai, Noura; Belkadi, Mustapha
This paper presents thermo-economic analyses of upgrading an existing Algerian gas turbine power plant into a CHP system. The proposed system includes a permanent upper steam Rankine cycle combined with a flexible ORC system during the summer period or a waste heat recovery exchanger during the winter period. The results revealed an increased energy efficiency by 16.9% and 21.59% for summer and winter configurations, respectively. Additionally, an increased exergy efficiency has been observed by 15.5% for both proposed configurations compared to the simple gas cycle with a positive environmental impact in terms of carbon footprint the reduction. The economic study highlights that the proposed solution is more attractive for international market rather than the local Algerian market that is characterised by a lower energy price.